Analysis of formatting channels prepared with manual file in rotary movement (Research, Society and Development, 2022)
Introduction: Seeking to streamline and facilitate the execution of endodontic treatment, studies improve techniques and instrumentation systems to perform procedures with less wear. The NiTi alloy has advantages over stainless steel. Its material considerably reduces the main flaws related to formatting, generating clinical application with better results. Objective: To compare the change in the width of root canals in artificial teeth using manual rotary nickel-titanium files with stainless steel K-files associated with Gates Gliden. Methodology: The study was carried out with thirty artificial lateral incisors divided into three groups. In the Control group, the teeth did not undergo any intervention. Group 1 was prepared with gates gliden burs and stainless steel manual files and group 2 with nickel titanium M files (Easy Equipamentos Odontologistas, Belo Horizonte, Brazil). Subsequently, radiographic images were obtained from all groups and the width of the canals were obtained at 5, 7, 10 and 14mm from the apex. Results. The mean widths found at 5mm, 7mm, 10mm and 14mm were respectively 0.303, 0408, 0723, 1.10 for the control group. Group 1 0.35, 047, 0786, 1.195. Group 2 0.423 , 0587, 0832, 1.267.Conclusion: Manual titanium nickel M files promoted less wear in the cervical third, when compared to the group where K-type files were used associated with Gliden gates burs. However, in the apical third, the M files promoted greater wear when compared to the K-type files associated with the gates gliden burs.